PENGEMBANGAN MEDIA PERMAINAN GO TEMAN UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN LOGIKA MATEMATIKA - Ifa Putri Wahyuhidayati; Mika Ambarawati (Jurnal Ilmiah Matematika Realistik, 2025)
This research aims to determine the feasibility of the monopoly media "MAK (FUN MATHEMATICS) ROUND" made from loose parts for children aged 5-6 years. This research is research using research and development methods or what is called Research and Development (R&D) using the ADDIE development model. The ADDIE instructional model is an instructional process that consists of five phases, namely analysis, design, development, implementation and evaluation. The subjects of this research were group A at Darul Hikmah Kindergarten, totaling 10 children consisting of 5 boys and 5 girls. In this research, media validation and observation validation of learning results were carried out first by material experts and media experts, after that the validator produced an evaluation of the media and observation sheets used. The aim is to test the suitability of the media used. The research instrument used in this research is an observation sheet that has been validated by experts. The observation sheet contains an assessment based on indicators of achievement in the development of mathematical logic in children in group A2. The indicators of the development of mathematical logic studied are knowing simple classifications, knowing numbers, knowing arithmetic operations, knowing geometric shapes. Learning media with the monopoly game MAK ROUND using loosepart media which was developed for group A2 children at DARUL HIKMAH Kindergarten has been validated by experts and received a percentage score of 92.72%. This shows that the MAK ROUND monopoly is declared worthy of being tested. Before being given treatment, the average acquisition of mathematical logic skills was below average, namely 66.8% and was declared incomplete. This means that children's mathematical logic is still low. After being given treatment, the average gain in mathematical logic skills in group A2 children increased to 84.7%. This shows that learning media using the MAK ROUND monopoly game is effective in improving mathematical logic skills in group A children aged 5-6 years.